Phytochemical Composition of 70% Ethanol Extract of Noni Fruit (MorindacitrifoliaL.) Using Ultrasound-Assisted Extraction Method and LC-MS Q-ToF - Lestari, Tri Puji; Kristianingsih, Ida; Purwani, Asih Imulda Hari; Nurhayati, Rachma; Kurniawati, Evi (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Noni (Morinda citrifolia L.) is a traditional medicinal plant that is widely used in the treatment of various degenerative diseases. However, scientific data regarding the composition of its bioactive compounds are still limited, especially those analyzed using a high-precision instrument approach. This study aims to identify the phytochemical composition in 70% ethanol extract of noni fruit using Liquid Chromatography-Mass Spectrometry (LC-MS) method. Extraction was performed by Ultrasound-Assisted Extraction (UAE) method and compound analysis using Q-ToF type LC-MS instrument with positive ionization mode. The results showed that noni extract contained 28 compounds, with 13 compounds successfully identified consisting of 7 alkaloids, 3 glycosides, 1 phenolic, 1 amino acid, and 1 aminoglycoside. The major compound identified was Methyl (5R)-2,3,4-tris-O-(methoxymethyl)-5-{2-[(2R,3R,4R,5R,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)-2-piperidinyl]ethyl}-α-D-xylopyranoside, belonging to the glycoside group with a molecular weight of 485.25 g/mol. These results indicate that noni fruit contains diverse secondary metabolite compounds with the dominance of alkaloid and glycoside compounds. This study contributes to providing primary data based on LC-MS technology on the chemical composition of Indonesian natural ingredients and can be a scientific basis for the development of medicinal plant-based pharmaceutical preparations with noni active ingredients.